Madrasah Nizamiyah: Telaah Historis Sebagai Lembaga Pendidikan dan Perang Politik-Ideologi - Ifendi, Mahfud (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2020)
As we know, Nidhamiyah madrasas have played an important role in the history of Islamic civilization to sustain the pace of development of Islamic education. This article aims to describe the history of the establishment of the Nidhamiyah madrasah as an educational institution and the chaotic establishment of this madrasa because it has rubbed off against political-ideological elements. This type of research is a qualitative research. In accordance with the object of the study of this article, this type of research is included in the category of library research. The result in this article is that the Nidhomiyah madrasa was founded in 447 H / 1055 M under the leadership of Tughril Bek from the Snowq dynasty. However, the main figure in the establishment of this madrasa was its vizier named Nizam al-Mulk. As an educational institution, of course this madrasah is the same as other madrasas in terms of management, educators, students, and learning methods. However, in terms of curriculum, this madrasah is a bit different because it contains Ashariyah theology material which is the main objective to defend the Sunni ideology of the Shia-Mu'tazilah ideology. After all, apart from having a role as an educational institution, this Nidhamiyah madrasah cannot be separated from the realm of the politics-ideology that underlies its birth.